2015
DOI: 10.1039/c5nj01103e
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a potential anti-hepatoma drug cis,cis,trans-[Pt(NH3)2Cl2(O2CCH2CH2COOH)-(OCONHC16H33)] with serum albumin – thermodynamic and conformational investigations

Abstract: In this paper, a potential anti-hepatoma Pt 4+ drug cis,cis,trans-[Pt(NH 3 ) 2 Cl 2 (O 2 CCH 2 CH 2 COOH)-(OCONHC 16 H 33 )] was synthesized and selected to investigate its binding to human serum albumin (HSA) by spectroscopy and molecular docking methods. Fluorescence spectra show that the Trp residue, the intrinsic fluorophore in HSA, was induced to a less hydrophobic microenvironment with the addition of the Pt 4+ compound, which induces the denaturation of HSA. Moreover, the fluorescence quenching mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…A negative value of the reaction enthalpy (Δ H = −2.85 kJ/mol) along with a positive entropy change (Δ S = 0.0179 kJ/mol) indicates that the quenching of the emission intensity of the 605 nm band was predominantly governed by the electrostatic interaction (Figure S3b,c). Moreover, as discussed above, the extent of the optical change was found to be dependent on the pH of the medium, and almost no interaction was observed below pH 4 (Figure b). The protonation at the carboxylic ends of the amino acid residues of SLNPV at low pH probably weakens the electrostatic interaction between 1 and SLNPV.…”
Section: Resultssupporting
confidence: 51%
“…A negative value of the reaction enthalpy (Δ H = −2.85 kJ/mol) along with a positive entropy change (Δ S = 0.0179 kJ/mol) indicates that the quenching of the emission intensity of the 605 nm band was predominantly governed by the electrostatic interaction (Figure S3b,c). Moreover, as discussed above, the extent of the optical change was found to be dependent on the pH of the medium, and almost no interaction was observed below pH 4 (Figure b). The protonation at the carboxylic ends of the amino acid residues of SLNPV at low pH probably weakens the electrostatic interaction between 1 and SLNPV.…”
Section: Resultssupporting
confidence: 51%
“…Furthermore, changes in the thermodynamic parameters were also evaluated by variable temperature studies. A negative value of Δ H with positive entropy change (Δ S ) suggested that the optical response (at 395 nm band) may be largely governed by electrostatic interactions. , To substantiate this argument, we monitored the changes in the zeta potential values of HaNPV upon gradual addition of 1 . In the absence of probe, HaNPV showed a highly negative zeta potential value at pH 7.4 because of the presence of a negatively charged polyhedrin protein surface.…”
Section: Resultsmentioning
confidence: 99%
“…More precisely, coupling of a Pt(IV) (bis)hydroxo species with an alkyl or aryl isocyanate affords the corresponding (bis)carbamate. Following optimization [260], allowing the reaction to be conducted in dimethylformamide and not in neat isocyanate, more than 60 different Pt(IV) species were thus prepared, arousing interest as possible anticancer agents (see Section 5) [261][262][263][264][265][266][267][268]. Reaction of hydroxido(oxido) ligands with organic isocyanates (Scheme 18d).…”
Section: Heteroleptic Carbamato Complexesmentioning
confidence: 99%
“…Platinum(IV) carbamato complexes with simple organic substituents on the nitrogen revealed a considerable cytotoxicity against various cancer cell lines, comparable or superior to that of the reference Pt(II) drug cisplatin [260,262,263]. A C 16 aliphatic chain (fatty acid-like) was introduced through the carbamato ligand to enhance cellular uptake [263,264,266,[366][367][368]. Following a different approach, the incorporation of a maleimide fragment enabled specific interactions with proteins (e.g., addition to thiol residues) for compounds showing a promising anticancer activity in vivo [261,268,369].…”
Section: Other Applicationsmentioning
confidence: 99%